OVERVIEW OF PAEDIATRIC BONE AND JOINT : A SYSTEMATIC REVIEW - Susilo, Dhanang (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Mercer Rang well observed, "Children are not young adults." Children and adults have different skeleton physiology and morphology. Depending on bone growth and remodelling, skeletal conditions should be treated differently. Because bone growth and modelling differ. Children's bones are more flexible than those of adults, so they can move more before they break. People often use the word "plastic deformation" to describe a condition in which the bone changes shape but does not break. Sometimes, the bone might just bend, causing a type of break called a torus fracture. Adults don't have these patterns because their bones are much less flexible and resistant to bending at angles than those of a growing skeleton. When two bones touch, they make a joint. Groups of joints can be made based on how they look or how they work. Functional classification is based on how much movement is allowed, while histological classification is based on the type of connective tissue that makes up most of the body. The mesoderm gives rise to joints, which are made up of bones and connective tissue. Bones can form either directly or indirectly through endochondral ossification or intramembranous ossification. The blood supply and nerve supply to each joint follow different rhythms.